Robustness of elastic properties in polymer nanocomposite films examined over the full volume fraction range. Issue 1 (December 2018) - Alonso-Redondo, E.; Belliard, L.; Rolle, K.; Graczykowski, B.; Tremel, W.; Djafari-Rouhani, B.; Fytas, G.
Abstract Polymers with nanoparticle inclusions are attractive materials because physical properties can be tuned by varying size and volume fraction range. However, elastic behavior can degrade at higher inclusion fractions when particle-particle contacts become important, and sophisticated measurement techniques are required to study this crossover. Here, we report on the mechanical properties of materials with BaTiO3 nanoparticles (diameters < 10 nm) in a polymer (poly(methyl methacrylate)) matrix, deposited as films in different thickness ranges. Two well-known techniques, time and frequency domain Brillouin light scattering, were employed to probe the composition dependence of their elastic modulus. The time domain experiment revealed the biphasic state of the system at the highest particle volume fraction, whereas frequency domain Brillouin scattering provided comprehensive information on ancillary variables such as refractive index and directionality. Both techniques prove complementary, and can in particular be used to probe the susceptibility of elastic properties in polymer nanocomposites to aging.